Pola Penerapan Pembelajaran Pendidikan Karakter Religius di Madrasah Tsanawiyah Ma’arif Nu Sutojayan - M. Nofian Hamdani (LPPM Politeknik Pratama, 2024)
Education basically aims to shape the character of students. The expected goals in education are stated in Law Number 20 of 2003 concerning the National Education System in article 3, the contents of which are